Efektivitas Media Puzzle dalam Meningkatkan Perilaku Pencegahan Covid-19 Pada Siswa di SDN Purwobinangun Kalasan - Ratna Lestari; Dewi Utari; Rahayu Iskandar (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: COVID-19 is an infectious disease that causes death globally. Prevention efforts are needed from all parties including school age children to break the chain of spread. Prevention can be done through the provision of information with appropriate media that suitable for the stage development, one of them is puzzle. Aim: The aim of this research is to identify the effect of puzzle as education media in improving COVID-19 prevention behavior in Public Elementary School, Purwobinangun, Kalasan, Sleman. Method: This was pra experimental study with pre post test without control group design. Total of 28 pupils in fourth grade involve as respondents. Researchers provide intervention in the form of health education about COVID-19 using puzzle for 2 weeks for 3 meetings in November 2021. The pretest questionnaires on knowledge of COVID-19 has been carried out with content validity with expert judgement and the I-CVI result is 1, which means the questionnaire is valid. While reliability use Inter Class Correlation (ICC) test with 0,840 which means reliable. Wilcoxon statistic test is used for bivariate analyzing. Result: obtained p value is 0,000 for knowledge, attitude, and behavior of COVID-19 prevention after the intervention. Conclusion: There is an effect of puzzle in improving COVID-19 prevention behavior. Health education media according to pupils characteristics can be used as an alternative education during the pandemy.